PENANGGULANGAN PELANGGARAN LALU LINTAS OLEH SATUAN LALU LINTAS POLRES BUKITINGGI TERHADAP PELAJAR - Anny Yuserlina (STIH Putri Maharaja, 2019)
The use of motorbike vehicles in the city of Bukittinggi is currently very rapid, but not accompanied by an increase will be aware and safe driving, especially for students at the high school/vocational/equivalent level, many who do not meet the safety standards in driving as stipulated in legislation. Bukittinggi is one city that also has a lot of both public and private schools, this also causes the violations committed by the instructor, including not having a SIM (Driving License), not wearing a helmet and changing vehicle standards. The purpose of this paper is to find out and analyze the response to traffic violations committed by students by the Bukittinggi Police Traffic Unit. The problem in this study is how to overcome traffic violations committed by students by the Bukittinggi Police Traffic Unit. To make this system more systematic, the writer uses an empirical juridical approach. The results of this study indicate that in overcoming traffic violations committed by students, the Bukittinggi police traffic unit conducts preventive and respite prevention. The factors that become obstacles in overcoming traffic violations committed by students are: The problem of legal awareness and traffic legal compliance among students is still lacking. Therefore it is necessary to look at the form of response so that it can overcome traffic violations.